(2a-4b-c)+(-2a-b-4c)=

Simple and best practice solution for (2a-4b-c)+(-2a-b-4c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2a-4b-c)+(-2a-b-4c)= equation:


Simplifying
(2a + -4b + -1c) + (-2a + -1b + -4c) = 0

Remove parenthesis around (2a + -4b + -1c)
2a + -4b + -1c + (-2a + -1b + -4c) = 0

Remove parenthesis around (-2a + -1b + -4c)
2a + -4b + -1c + -2a + -1b + -4c = 0

Reorder the terms:
2a + -2a + -4b + -1b + -1c + -4c = 0

Combine like terms: 2a + -2a = 0
0 + -4b + -1b + -1c + -4c = 0
-4b + -1b + -1c + -4c = 0

Combine like terms: -4b + -1b = -5b
-5b + -1c + -4c = 0

Combine like terms: -1c + -4c = -5c
-5b + -5c = 0

Solving
-5b + -5c = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '5c' to each side of the equation.
-5b + -5c + 5c = 0 + 5c

Combine like terms: -5c + 5c = 0
-5b + 0 = 0 + 5c
-5b = 0 + 5c
Remove the zero:
-5b = 5c

Divide each side by '-5'.
b = -1c

Simplifying
b = -1c

See similar equations:

| 10x-6=-25 | | 3x+6-9x=30 | | f(x)=-x+10 | | 10x^3-25x^2+20= | | 3(y+5)=32 | | 5m+5.25=42.75 | | -1-2g=1 | | -20+12r+6q-2r-3q-26= | | 0/27=x | | 2(a+2b)-(a-b)= | | 9+4r=1 | | 19=19h-19 | | 5=v+1 | | 1/6d+2/3=1/4(d-2) | | -4+15=11 | | sinA=0.5 | | 7x-8-5x=0 | | 118=-5(-4-4p)-6p | | -4+15=x | | 7c-2c=42 | | x-6-17=-13 | | -7z+4+16-8z= | | X^3-6x+10x-8=0 | | 15=12k-9 | | a+(a+10)=16 | | -4c+9(3c+5)= | | 10p+18=-12 | | 13q+48=-3q | | -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 |

Equations solver categories